Nutrition Education on Food Choices of Secondary School Students in Lagos State, Nigeria - Owolabi, Habeeb Ladi; Banjoko, Oluwayemi O.; Adekanmbi, Barakat O.; Amusa, Modinot F.; Omolewa, Musiliu O. (NIU Journal of Social Sciences; Vol 6 No 3 (2020): KIU Journal of Social Sciences, Vol. 6 No. 3, September 2020, 2020)
Adolescents face the risks of diet-related diseases during transition to adulthood. These diseases could lead to morbidity or mortality when dietary information is not within their reach to improve their dietary behaviour for the prevention of these diseases. This study examined nutrition education on food choices of secondary school students in Lagos Island Local Government Area, Lagos State, Nigeria. Pre test - post test experimental and control group designs were used for the study. The study population comprised 5,946 senior secondary school students in Lagos Island Local Government Area. Multistage sampling technique was used to select one hundred and twenty one (121) participants from two senior secondary schools who were assigned into two groups, namely experimental and control groups. Research instrument is a modified Nutritional Behaviour Questionnaire (r=0.73). Researcher Developed Nutrition Education Manual was also used for the intervention sessions. One research hypothesis was formulated to guide the study. The data collected was analysed using Analysis of Covariance. The hypothesis was tested at 0.05 level of significance. The result of data analysis revealed that the hypothesis was rejected. The findings showed that nutrition education significantly improves food choices of the students. It was concluded that nutrition education improves the food choices of students. The study recommended that all secondary school students should be exposed to nutrition education to improve their choices of food for consumption. This will help improve their behaviour and also reduce the risk of diet related chronic diseases. Keywords: Behaviour, Diets, Food Choices, Nutrition Education, Secondary School Students.